Time-Sensitive Smart Cities: Addressing Smart City Challenges With TSN - Rui Eduardo Lopes; Duarte Raposo; Rodrigo Martins; Susana Sargento (IEEE Access)
As cities transition into interconnected hubs of technology, the need for efficient time management across diverse interconnected devices becomes a requirement for supporting critical services for emergency, traffic, and other use cases. Time-sensitive network (TSN) emerges as a promising solution, offering standards and mechanisms to synchronize and regulate time-critical traffic in smart city infrastructures. This study researches the main use cases, key standards and mechanisms of TSN, evaluating their feasibility and adaptability to the heterogeneous equipment present in an urban environment of a smart city infrastructure. Through experimental assessments, this article demonstrates the efficacy of TSN-based solutions and also discusses hardware enhancements that complement TSN protocols, improving precision and resource utilization to ensure criticality in urban connectivity, enabling precise control over traffic conditions and service delivery towards the future smart city, as an environment of interconnected things. Moreover, we propose a classification of nine traffic categories to encompass the various traffic flows in a smart city deployment, and validate the application of time-aware and credit-based shaping of all nodes in the network according to the type of service. Results show that TSN is a valid choice to manage mixed-criticality of services in a smart city.